Preparation of Macroscopic Block‐Copolymer‐Based Gyroidal Mesoscale Single Crystals by Solvent Evaporation. Issue 40 (22nd August 2019) - Susca, Ethan M.; Beaucage, Peter A.; Thedford, R. Paxton; Singer, Andrej; Gruner, Sol M.; Estroff, Lara A.; Wiesner, Ulrich
Abstract: Properties arising from ordered periodic mesostructures are often obscured by small, randomly oriented domains and grain boundaries. Bulk macroscopic single crystals with mesoscale periodicity are needed to establish fundamental structure–property correlations for materials ordered at this length scale (10–100 nm). A solvent‐evaporation‐induced crystallization method providing access to large (millimeter to centimeter) single‐crystal mesostructures, specifically bicontinuous gyroids, in thick films (>100 µm) derived from block copolymers is reported. After in‐depth crystallographic characterization of single‐crystal block copolymer–preceramic nanocomposite films, the structures are converted into mesoporous ceramic monoliths, with retention of mesoscale crystallinity. When fractured, these monoliths display single‐crystal‐like cleavage along mesoscale facets. The method can prepare macroscopic bulk single crystals with other block copolymer systems, suggesting that the method is broadly applicable to block copolymer materials assembled by solvent evaporation. It is expected that such bulk single crystals will enable fundamental understanding and control of emergent mesostructure‐based properties in block‐copolymer‐directed metal, semiconductor, and superconductor materials. Abstract : A simple procedure generates single crystals from evaporation‐induced block‐copolymer self‐assembly with 1000‐fold improvement in grain size, such that macroscopic single crystals are isolated. These crystals have a complex, bicontinuous, cubic architecture, known as the double gyroid, and can be converted into freestanding porous refractory ceramic monoliths that have single‐crystal‐like optical and fracture properties.